Neo-Rural Scape Lines in Spanish Contemporary Literature - Mora, Vicente Luis (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
In the last two decades of 21th Century, Spanish literature has oscillated between two socio-geographic poles: on the one hand, recovering affection for local and even rural atmospheres through placing storylines in recognizable rustic spaces; on the other hand, through a clear consciousness of the globalization processes in which the western societies are now involved, notwithstanding recent phenomena which seem in opposition with this dynamic, such as British’s Brexit. In this text we will comment those tendencies, specially the so called ‘neorrural’, in order to verify up to what point they can have connections with the glocal perspective, with literary characteristics of their own.
Keywords: Literature; Globalization; Neo-rural; Glocal; Nationalism